Trade reforms and food security : country case studies and synthesis - Thomas, Harmon C. (Food and Agriculture Organization of the United Nations, 2006)
The linkage between trade-related policy reforms and food security is of vital concern to many developing countries. This volume summarizes the results of a study designed to show how trade and associated economic policy reforms have affected the agriculture sector and food security of farmers in a range of developing countries. The approach taken is to observe actual performance in fifteen countries that have undergone policy reform in the past few years, and to search for explanatory factors, rather than to project the presumed consequences of reforms through models of economic behaviour. The 15 countries selected are representative of different regions of the world, and different stages of development: Cameroon, Chile, China, Ghana, Guatemala, Guyana, India, Kenya, Malawi, Morocco, Nigeria, Peru, Senegal, Tanzania, and Uganda.